ZAKAT: Government Fiscal Policy Instruments in the Covid-19 Pandemic - Nurafifah, Yamuna (Munazzama: Journal of Islamic Management and Pilgrimage, 2021)
This study is a literature research that uses qualitative methods, the data is presented in a narrative and focuses on the direction of the description. Sources of data come from primary and secondary data sources. This study focuses on an overview of zakat in Islamic economics and zakat in Indonesian legal policy in order to find out zakat from the perspective of Islamic economics and law in Indonesia. Instruments of fiscal policy in Indonesia to determine the fiscal policy of the Indonesian government. The relevance of zakat as an instrument of fiscal policy in Indonesia during the covid-19 pandemic to find out the potential of zakat as a government policy instrument in the covid-19 pandemic. The results of the study are zakat in Islamic economics including:  source of state revenue while in Indonesian law it is not included in the state budget. The reflection of the Indonesian government's fiscal policy is the APBN. Zakat has great potential, role and benefits as an instrument of government fiscal policy in dealing with the Covid-19 pandemic. Modern management and laws are still needed to maximize zakat collection.